RADIO FREQUENCY DATA IDENTIFICATION TECHNOLOGY: POTENTIAL FOR USE IN FASHION INDUSTRY SUPPLY CHAINS - N. Yu. Barkova; O. A. Borodina (Вестник университета)
The issues related to the use of RFID technology in the supply chains of the fashion industry have been considered. The prospects of using this technology in the supply chains of the fashion industry are related to a number of features that characterize the industry. Such features include a high product range and its rapid turnover, rapid changes in purchasing preferences, and the need to respond quickly to changes in consumer demand. Traditionally, RFID technology is used to identify data in warehouse logistics or company distribution system, but the scope of application of this technology in the fashion industry is constantly expanding. The technology can be used to increase the transparency and security of supply chains, marketing research and in other areas. It has been also emphasized that the joint application of RFID technology with other digital technologies, such as blockchain, is promising. Some restrictions related to the application of technology in the industry have been also highlighted.